ANALISIS KERUSAKAN STRUKTUR PERKERASAN DAN TANAH DASAR PADA RUAS JALAN SEMEN – NGLUWAR KABUPATEN MAGELANG - EKO WIYONO (Politeknik Negeri Jakarta, 2013)
ABSTRACT Evaluation of the condition of the road pavement structure required prior to maintenance and repair . This study aims to determine the type of damage , extent of damage , and determine how to repair the damage road pavement cement - ngluwar . The research includes assessing pavement conditions visually using pci method by dividing the road into 52 segments , dynamic cone penetrometer test ( dcp ) subgrade , test california bearing ratio ( cbr ) field in base layer , traffic surveys , and analysis using the additional thick layer methods of aashto , 1993 . The results showed that , the visual type of damage that occurs is alligator cracking , block cracking , depression , long and transverse cracking , patching , raveling & weatering , rutting , extensive damage to 25.30 % , the dominant type alligator cracking damage 14.23 % of the total area and obtained an average value of 50.06 pci or pavement conditions are (fair ) . Dcp test results of subgrade cbr values obtained on average 10.33 % , the results of the field test cbr cbr base layer is obtained on average 65.70 % , the survey results obtained lhr traffic as much as 2397 vehicles / day . Repair damage in accordance with the location , type , and extent of the damage , it is better if done additional coating ( overlay ) , a thick layer of additional analysis , with a design life of 10 years acquired an additional layer 5cm thick . Keywords : pavement, condition, damage, subgrade, repairs